The immunophenotype of mast cells and its utility in the diagnostic work‐up of systemic mastocytosis. Issue 1 (7th November 2014) - Teodosio, Cristina; Mayado, Andrea; Sa´nchez‐Mun~oz, Laura; Morgado, Jose´ M.; Jara‐Acevedo, Mari´a; A´lvarez‐Twose, Ivan; Garci´a‐Montero, Andre´s C.; Matito, Almudena; Caldas, Caldas; Escribano, Luis; Orfao, Alberto
Abstract : Review of normal/reactive mast cell maturational profiles for the identification of aberrant phenotypes used in the diagnostic work‐up of systemic mastocytosis. Abstract : SM comprises a heterogeneous group of disorders, characterized by an abnormal accumulation of clonal MCs in 1 or more tissues, frequently involving the skin and BM. Despite the fact that most adult patients (>90%) carry the same genetic lesion (D816V KIT mutation), the disease presents with multiple variants with very distinct clinical and biologic features, a diverse prognosis, and different therapeutic requirements. Recent advances in the standardization of the study of BM MC by MFC allowed reproducible identification and characterization of normal/reactive MCs and their precursors, as well as the establishment of the normal MC maturational profiles. Analysis of large groups of patients versus normal/reactive samples has highlighted the existence of aberrant MC phenotypes in SM, which are essential for the diagnosis of the disease. In turn, 3 clearly distinct and altered maturation‐associated immunophenotypic profiles have been reported recently in SM, which provide criteria for the distinction between ISM patients with MC‐restricted and multilineage KIT mutation; thus, immunphenotyping also contributes to prognostic stratification of ISM, particularly when analysis of the KIT mutation on highly purified BM cells is not routinely available in the diagnostic work‐up of the disease.